Exploring Paintings Related to Renaissance Religious Culture - Sun, Xuechen (Transactions on Social Science, Education and Humanities Research, 2024)
This study focuses on the study and appreciation of religious paintings in the Renaissance, the main reason for studying this aspect is that it is more interested in the collision between art and society as well as the connection between art and religion in the history of art. This aspect is also a very important part of the Renaissance, which is related to that period of history and the creative process of the painters at that time; this study mainly focuses on the analysis of religion and famous paintings in the Renaissance period; the method of literature analysis was used to find and read the relevant information and literature, and the advantage of this method is that it can analyze the religious belief system and the influence and the existence of paintings in the society at that time. The system and the influence of religious culture in the paintings, that is, the use of literature analysis method to analyze the content of the paper, conducive to research; through the study found that religious culture is one of the important elements of the Renaissance, but also changed the style of the previous paintings and the form of creation. It has also become one of the most important components and changes in the history of humanities and society.